Evaluation of interface design: a case study of CSC134 e-learning module courseware / Nur Hafizi Ghazali - Ghazali, Nur Hafizi (2011)
The evaluation of interface design of a learning material is important to identify its usability problems and to understand learner experience with the courseware and where difficulties, to find the way to solve it. This research covers the usability evaluation of CSC 134 e-learning module courseware since it has never been evaluated before. Its purpose is to suggest the improvements for the interface design of CSC 134 e-learning module courseware. The questionnaire is distributed during the usability evaluation to collect data regarding their comments and recommendations. This study uncovers the criteria of good user interface design so then the improvements of the bad criteria of the e-learning module courseware design can be suggested. The result of this study is very beneficial to help learner to gain better learning and also for the designer to design the interface design of CSC 134 e-learning module courseware.